Inner Product over Fuzzy Matrices - Nagoor Gani, A.; Kannan, K.; Manikandan, A.R. (Hindawi, 2016)
The purpose of this study was to introduce the inner product over fuzzy matrices. By virtue of this definition, 𝛼-norm is defined and the parallelogram law is proved. Again the relative fuzzy norm with respect to the inner product over fuzzy matrices is defined. Moreover Cauchy Schwarz inequality, Pythagoras, and Fundamental Minimum Principle are established. Some equivalent conditions are also proved.